Sequelae and Comorbidities of COVID-19 Manifestations on the Cardiac and the Vascular Systems - Batta, Yashvardhan; King, Cody; Johnson, John; Haddad, Natasha; Boueri, Myriam; Haddad, Georges (Frontiers in Physiology, 2022)
COVID-19 patients with pre-existing cardiovascular conditions are at greater risk of severe illness due to the SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) virus. This review evaluates the highest risk factors for these patients, not limited to pre-existing hypertension, cardiac arrhythmias, hypercoagulation, ischemic heart disease, and a history of underlying heart conditions. SARS-CoV-2 may also precipitate de novo cardiac complications. The interplay between existing cardiac conditions and de novo cardiac complications is the focus of this review. In particular, SARS-CoV-2 patients present with hypercoagulation conditions, cardiac arrhythmias, as significant complications. Also, cardiac arrhythmias are another well-known cardiovascular-related complication seen in COVID-19 infections and merit discussion in this review. Amid the pandemic, myocardial infarction (MI) has been reported to a high degree in SARS-CoV-2 patients. Currently, the specific causative mechanism of the increased incidence of MI is unclear. However, studies suggest several links to high angiotensin-converting enzyme 2 (ACE2) expression in myocardial and endothelial cells, systemic hyper-inflammation, an imbalance between myocardial oxygen supply and demand, and loss of ACE2-mediated cardio-protection. Furthermore, hypertension and SARS-CoV-2 infection patients’ prognosis has shown mixed results across current studies. For this reason, an in-depth analysis of the interactions between SARS-CoV2 and the ACE2 cardio-protective mechanism is warranted. Similarly, ACE2 receptors are also expressed in the cerebral cortex tissue, both in neurons and glia. Therefore, it seems very possible for both cardiovascular and cerebrovascular systems to be damaged leading to further dysregulation and increased risk of mortality risk. This review aims to discuss the current literature related to potential complications of COVID-19 infection with hypertension and the vasculature, including the cervical one. Finally, age is a significant prognostic indicator among COVID-19 patients. For a mean age group of 70 years, the main presenting symptoms include fever, shortness of breath, and a persistent cough. Elderly patients with cardiovascular comorbidities, particularly hypertension and diabetes, represent a significant group of critical cases with increased case fatality rates. With the current understanding of COVID-19, it is essential to explore the mechanisms by which SARS-CoV-2 operates to improve clinical outcomes for patients suffering from underlying cardiovascular diseases and reduce the risk of such conditions de novo.